Bernalar dalam Lingkaran?: Menjawab Problem Sirkularitas Doktrin Kesaksian Internal Roh Kudus - Sulistio, Thio Christian (Veritas : Jurnal Teologi dan Pelayanan, 2020)
Circular Reasoning?: Answering the Problem of Circularity in the Doctrine of Internal Witness of the Holy Spirit. The doctrine of the internal testimony of the Holy Spirit was used by John Calvin to explain why Christians can believe in the Bible as the word of God. However, this doctrine is not free from problems especially related to the problem of circular reasoning, subjectivism, and is considered to ignore evidence and arguments. This paper tries to answer these problems by first discussing the nature and mechanism of the internal testimony of the Holy Spirit. Secondly, it attempts to answer these problems by using the concept of multilevel knowledge and acknowledging the existence of epistemic circularity. With the help of these concepts, the author will show that these problems can be answered well.